Structural analysis of a feline norovirus protruding domain - Singh, Bishal; Glatt, Sebastian; Ferrer, Jean-Luc; Koromyslova, Anna D.; Leuthold, Mila; Dunder, Jessica; Hansman, Grant S. (Virology, 2015)
Norovirus infects different animals, including humans, mice, dogs, and cats. Here, we show an X-ray crystal structure of a feline GIV.2 norovirus capsid-protruding (P) domain to 2.35Å resolution. The feline GIV.2 P domain was reminiscent of human norovirus P domains, except for a novel P2 subdomain α-helix and an extended P1 subdomain interface loop. These new structural features likely obstructed histo-blood group antigens, which are attachment factors for human norovirus, from binding at the equivalent sites on the feline GIV.2 P domain. Additionally, an ELISA showed that the feline GIV.2 was antigenically distinct from a human GII.10 norovirus.